The Role of Spiritual Health and Social Support in Predicting Nurses' Quality of Life - Seyedeh Azar Chavoshian; Babak Moeini; Saeed Bashirian; Javad Feradmal (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Spiritual health coordinates different aspects of life with one another, and reinforces compatibility and psychological function. Quality of life can be affected by psychological-spiritual factors and working environment. This study was conducted to determine the role of social support and spiritual health in nurses' quality of life. Materials and Methods: This descriptive-correlative study was conducted among 200 working nurses in two teaching hospitals that were randomly selected in the city of Hamedan. All nurses in the two hospitals were recruited. The data collection tools were World Health Organization Quality of life Questionnaire (WHOQOL-BRIEF) and Palotzin and Elison Spiritual and Social Support Questionnaires. Data were analyzed by multiple regression test in SPSS-18 software. Results: The mean of age of nurses in this study was 33.86±6.63. Regression analysis showed that informative support and instrumental support had a significant role in predicting the quality of life and only religious health component had a meaningful effect on nurses' quality of life. Conclusion: According to our findings, it is necessary to provide educational interventions and training packages to improve nurses´ spiritual health and quality of life.